Diagnosis of piston multistage compressor by parameters of working process - Кучер, О. Г.; Орлов, І. О.; Снєгірьов, М. О. (Proceedings of National Aviation University (archive), 1999)
Considered are the methods of diagnosis of multistage compressor condition by parameters of working process. The methods of smoothing, standardization and identification of deviation from normal condition of compressor are described. Performed is the description of diagnosis of compressor in real working conditions. The expedience of method is confirmed in the operation